PENGEMBANGAN VIDEO PEMBELAJARAN MENGGUNAKAN SOFTWARE WONDERSHARE FILMORA PADA MATA PELAJARAN SEJARAH - Fama Gala Tea; Syarifuddin Syarifuddin; Adhitya Rol Asmi (Akademika : Jurnal Teknologi Pendidikan, 2022)
The study discusses “Development Of Learning Videos Using Wondershare Filmora Software In History Subject Class X State Senior High School 3 Palembang”. The purpose of this study was to determine the stages of development of video learning media using Wondershare Filmora Software.and to determine the effect of the effectiveness of video media developed using Wondershare Filmora Software. This type of research is Research and Development (R&D) with the Allesi and Trollip development model. The research was conducted at state Senior High school 3 Palembang.The conclusion of the study shows that; (1) Video media using Wondershare Filmora Software in class X history of State High School 3 Paelmbang can be said to be valid if it has been tested through the validity of 3 expert reviews and with input from experts, and field tests to determine the practicality of the media and efficient media. (2) There is an increase in student learning outcomes by 24.66%, so the value obtained from Ngain is 0.46 which is in the medium category